Thyroid Ultrasound and Ultrasound-Guided FNA Second Edition - Baskin, H. Jack.; Duick, Daniel S.; Levine, Robert A.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Thyroid Ultrasound and Ultrasound-Guided FNA, Second Edition is a "user friendly" book for the clinician, using ultrasound in the evaluation and management of thyroid disease. It reviews new information regarding ultrasound and the subtleties one needs to know in the application of this technique. With abundant ultrasound images, it demonstrates how ultrasound is integrated with the patient history, physical exam, and other thyroid tests (especially FNA biopsy) providing information on improving care. The book presents numerous, new innovative uses of ultrasound that are being implemented worldwide. Foreword by Leonard Wartofsky, MD, MACP, Chairman, Department of Medicine, Washington Hospital Center, Washington, DC.
History of Thyroid Ultrasound -- Thyroid Ultrasound Physics -- Doppler Ultrasound -- Anatomy and Anomalies -- Thyroiditis -- Ultrasound of Thyroid Nodules -- Ultrasound-Guided Fine-needle Aspiration of Thyroid Nodules -- Ultrasound in the Management of Thyroid Cancer -- Parathyroid Ultrasonography -- Contrast-Enhanced Ultrasound in the Management of Thyroid Nodules -- Percutaneous Ethanol Injection (PEI): Thyroid Cysts and Other Neck Lesions -- Laser and Radiofrequency Ablation Procedures -- High Intensity Focused Ultrasound (HIFU) Ablation Therapy for Thyroid Nodules -- Ultrasound Elastography of the Thyroid.
Keywords: MEDICINE; RADIOLOGY, MEDICAL; DIAGNOSIS, ULTRASONIC; INTERNAL MEDICINE; ENDOCRINOLOGY; ONCOLOGY; OTORHINOLARYNGOLOGY; MEDICINE & PUBLIC HEALTH; ENDOCRINOLOGY; DIAGNOSTIC RADIOLOGY; ULTRASOUND; ONCOLOGY; OTORHINOLARYNGOLOGY; INTERNAL MEDICINE